ASEAN's Role in Addressing the Myanmar Crisis: Challenges and Prospects for Regional Peace - Abiyyu Ahnaf Bayana Abi; Diwan Azka Purwananda Diwan Azka Purwananda; Muhammaad Daffa Pratama Muhammad Daffa Pratama; Muhammad Adjie Akbar Muhammad Adjie Akbar; Elly Nurlia Elly Nurlia (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The military coup in Myanmar on February 1, 2021, marked a critical setback for the country’s democratic transition and triggered one of the most severe political and humanitarian crises in Southeast Asia. This paper aims to analyze ASEAN’s effectiveness in addressing the Myanmar crisis through the implementation of the Five-Point Consensus (5PC). Using a qualitative approach and library research method, the study explores ASEAN’s normative and institutional limitations in responding to internal conflicts that have regional implications. The research employs Normative Institutionalism and Regional Security Complex Theory as analytical frameworks to explain how ASEAN’s fundamental principles particularly non-interference and consensus decision making shape the organization’s cautious and non-coercive diplomacy. The findings reveal that ASEAN’s response remains largely symbolic and lacks enforcement mechanisms, resulting in low implementation effectiveness. Factors such as institutional weaknesses, normative constraints, and divergent geopolitical interests among member states further hinder progress. The study proposes a Five-Point Consensus Plus (5PC+) model, emphasizing measurable indicators, independent monitoring, and civil society engagement to strengthen ASEAN’s peacebuilding capacity. In conclusion, ASEAN must undergo institutional reform and reinterpret its norms to enhance its credibility as a regional peace and security actor.